Improved quality of life and glycemic management after switching from conventional rapid-acting insulin to ultra-rapid lispro in patients with diabetes - Yuriko Hajika; Yuji Kawaguchi (Metabolism Open, 2025)
For optimal postprandial glucose (PPG) management, rapid-acting insulin analogs (RAA) should be administered 15 min before a meal; however, this may not be possible for some individuals. Ultra-rapid lispro (URLi) can be administered 0–2 min before or <20 min after a meal, which may improve patient satisfaction and PPG management. In this pilot study, we evaluated changes in quality of life (QOL) and glycemic management among Japanese outpatients with type 2 diabetes mellitus (T2DM) who switched from RAA to URLi. We enrolled 12 outpatients with T2DM and evaluated QOL using the insulin therapy-related (ITR) QOL questionnaire. The primary endpoint was the change in ITR-QOL scores at 12–15 weeks. Endpoints were evaluated using the one-sample Wilcoxon signed rank test or paired t-tests. URLi was associated with a significant increase in ITR-QOL (+15.1 ± 16.1 points, p < 0.01), perception (+7.2 ± 6.9 points, p < 0.01), and status (+7.9 ± 9.5 points, p < 0.05) scores. At 12–15 weeks, the time in range significantly increased (+8.3 ± 9.2, p < 0.05), time above range significantly decreased (−7.7 ± 10.2, p < 0.05), and time below range showed no significant changes. Thus, switching from RAA to URLi significantly improved ITR-QOL questionnaire scores. In summary, URLi is an effective treatment alternative, providing flexible timing, improved glycemic management, and enhanced patient satisfaction.